Formin-2 drives polymerisation of actin filaments enabling segregation of apicoplasts and cytokinesis in Plasmodium falciparum - Stortz, Johannes Felix; Del Rosario, Mario; Singer, Mirko; Wilkes, Jonathan M; Meissner, Markus; Das, Sujaan (eLife, 2019)
In addition to its role in erythrocyte invasion, Plasmodium falciparum actin is implicated in endocytosis, cytokinesis and inheritance of the chloroplast-like organelle called the apicoplast. Previously, the inability to visualise filamentous actin (F-actin) dynamics had restricted the characterisation of both F-actin and actin regulatory proteins, a limitation we recently overcame for Toxoplasma (Periz et al, 2017). Here, we have expressed and validated actin-binding chromobodies as F-actin-sensors in Plasmodium falciparum and characterised in-vivo actin dynamics. F-actin could be chemically modulated, and genetically disrupted upon conditionally deleting actin-1. In a comparative approach, we demonstrate that Formin-2, a predicted nucleator of F-actin, is responsible for apicoplast inheritance in both Plasmodium and Toxoplasma, and additionally mediates efficient cytokinesis in Plasmodium. Finally, time-averaged local intensity measurements of F-actin in Toxoplasma conditional mutants revealed molecular determinants of spatiotemporally regulated F-actin flow. Together, our data indicate that Formin-2 is the primary F-actin nucleator during apicomplexan intracellular growth, mediating multiple essential functions.